Abordagens das necessidades humanas e das capacitações : uma aplicação da metodologia de Alkire e Foster para o estudo da pobreza multidimensional em Minas Gerais nos anos de 2000 e 2010 - Silva, Ana Márcia Rodrigues da (2015)
According to the conventional literature, poverty can studied based on a single dimension, usually represented by a monetary variable. However, the approaches of human needs and the capabilities provide a broader theoretical framework for their study. According to these approaches, poverty is multidimensional and these aspects need to consider by empirical studies on the subject. Therefore, this thesis aims to discuss the multidimensional aspects of poverty by means of the theoretical approaches of human needs and the capabilities and raise the methodological challenges around your measurement, in order to estimate and decompose the multidimensional poverty in Minas Gerais in the years 2000 and 2010. Using data from the demographic Censuses of those years, it employed a methodology to build multidimensional poverty indices proposed by Alkire and Foster (2007). The central questions of this work are: What are the dimensions that may incorporated into the empirical analysis of poverty? In which regions of the State of Minas Gerais the multidimensional poverty is higher? What are the dimensions deprive to a greater extent mining families? Throughout the study, it found that the dimensions of poverty chosen, primarily, as the theoretical aspects that do not provide a fixed list of essential dimensions, which make room for the appropriate to the realities studied. In this paper, the dimensions used in the analysis were economic vulnerability, occupational conditions, educational characteristics, housing conditions, health conditions, absence of goods and health. These dimensions are critical because, if they are not met, limit the ability of development of human beings in society. It understood that these dimensions are not sufficient for understanding the multidimensional poverty, but already provide results more consistent than the unidimensional vision. The analysis of multidimensional poverty in Minas Gerais allowed evidence that there was a reduction of poverty in the State in the years analyzed. In comparison with unidimensional indicators, multidimensional indicators were slightly divergent in terms of ranking, but generally far superior. Multidimensional poverty appeared higher in the meso regions of the Jequitinhonha, North of Minas, and Vale do Mucuri; and in the micro regions of Grão Mogol, Januária, Salinas, Araçuaí, and Peçanha. With the decomposition of poverty by subgroups, identified that some localities in multidimensional poverty is less severe contribute a lot to the total poverty, as the meso region Metropolitan of Belo Horizonte. Finally, the decomposition of poverty by dimensions, demonstrated that the dimension absence of goods, in general, was the one that contributed to poverty in the State, followed by the dimension of educational characteristics. Sanitary conditions have contributed more to the poverty of the poorest localities that the less poor. Meanwhile, the health dimension obtained greater participation in poverty of localities less poor than the poorest. It concluded that the social in heterogeneities in Minas Gerais remain and are broad with the study of multidimensional poverty, since the State is home to ups and low levels of poverty and that poverty profiles are distinct. All these results are relevant to public policy development.